2015
DOI: 10.1287/isre.2014.0564
|View full text |Cite
|
Sign up to set email alerts
|

Early to Adopt and Early to Discontinue: The Impact of Self-Perceived and Actual IT Knowledge on Technology Use Behaviors of End Users

Abstract: For organizations to achieve the benefits of new IT systems their users must adopt and then actually use these new systems. Recent models help to articulate the potentially different explanations for why some users will adopt and then continue using new technologies, but these models have not explicitly incorporated IT-knowledge. This is particularly important in contexts where the user base may be non-IT professionals-i.e. the users may vary substantially in their basic IT-knowledge. We draw upon psychology t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Our findings show that triggers relate to users' efforts to incorporate the new IT artefact into their workflow and adapting their interaction style to new requirements. Our study confirms previous studies as far as workarounds (e.g., Alter, 2014; Barrett, 2018; Choudrie et al, 2016), and discontinued use (e.g., Aggarwal, Kryscynski, Midha, & Singh, 2015; Turel, 2016) are concerned, in terms of potential behavioural outcomes following disconfirmation. We, however, reveal an additional user practice, that of reframing initial expectations, whereby users update their understanding of the device and appreciate it under a new light.…”
Section: Introductionsupporting
confidence: 90%
“…Our findings show that triggers relate to users' efforts to incorporate the new IT artefact into their workflow and adapting their interaction style to new requirements. Our study confirms previous studies as far as workarounds (e.g., Alter, 2014; Barrett, 2018; Choudrie et al, 2016), and discontinued use (e.g., Aggarwal, Kryscynski, Midha, & Singh, 2015; Turel, 2016) are concerned, in terms of potential behavioural outcomes following disconfirmation. We, however, reveal an additional user practice, that of reframing initial expectations, whereby users update their understanding of the device and appreciate it under a new light.…”
Section: Introductionsupporting
confidence: 90%
“…Turel () noted that discontinuance use of ICT merits its own theoretical foundations, usually separating from the continuance use (Aggarwal, Kryscynski, Midha, & Singh, ; Birnholtz, ). In the context of SNS, a number of studies, as shown in Table , have been conducted to examine the possible factors driving the discontinuance of SNSs (e.g., Cho, ; Luqman, Cao, Ali, Masood, & Yu, ; Zhang, Zhao, Lu, & Yang, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the SNS user exodus, the user's behavioral pattern usually involves a dynamic process from the initial adoption to the final abandonment, during which various factors (i.e., individual, social, and technological) interact with each other. The most interesting part of this phenomenon is what happens during the adoption‐abandonment procedure (Aggarwal et al, ; Birnholtz, ). As indicated in Table , prior research has identified some antecedents to the SNS discontinuance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Often, these studies draw from theories, such as the Technology Acceptance Model (Davis and Warshaw 1989 ), the Unified Theory of Acceptance and Use of Technology (Venkatesh et al 2003 ) and their variations (Kim and Garrison 2009 ; e.g., Venkatesh et al 2011 ; Venkatesh and Davis 2000 ). These theories place the emphasis on the factors that drive user decision with regard to the acceptance or rejection of the technology (Aggarwal et al 2015 ). However, because these theories place the emphasis on the preliminary stages of user interaction, less or no emphasis is inescapably given in how users actually make use of the technology, which exerts a greater impact on its viability (Venkatesh et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%